“Traveling the Graciana”. Methodological aspects and results of the field work of the LRA site - Rodriguez Oviedo, Melisa (Revista del Museo de Antropología, 2018)
In this note is in the Valley of Ambato, Catamarca, Argentina. This site was studied with the purpose of deepening the works carried out in the eastern slope of the valley (La Graciana mountain range). In order to achieve this objective, fieldwork (survey and survey) is carried out during the months of October and November 2014. As a result of these activities, registrars are registered and they identify different types of structures (enclosures, corrals and canals), which recover ceramic and lithic materials on the surface. This work allowed to identify an agricultural sector mainly to the agricultural methods that a priori would be in agreement with the proposed productive configuration for the valley. The information obtained from this work suggests that LRA was exclusively focused on agricultural production and that it constituted a particularity within the agro-pastoral model proposed for the area under study. In this way, it is possible to think of this system not as a non-homogeneous whole, but with variants that can respond to social, political, environmental and / or chronological issues.